Childhood Nephrotic Syndrome Complicated by Catastrophic Multiple Arterial Thrombosis Requiring Bilateral Above-Knee Amputation - Togashi, Hayato; Shimosato, Yuko; Saida, Ken; Miyake, Noriko; Nakamura, Takeshi; Ito, Shuichi (Frontiers in Pediatrics, 2020)
Background Thromboembolic events are rare but critical complications in childhood nephrotic syndrome. The veins are more commonly affected, while arterial thrombosis is extremely rare but often life-threatening. Herein, we describe the clinical course of a 10-year-old girl with catastrophic multiple arterial thrombosis at the primary onset of nephrotic syndrome who underwent bilateral above-knee amputation. Case diagnosis/treatment A previous healthy 10-year-old girl contracted the influenza B virus. Five days later, she suddenly developed severe ischemia in both legs. Physical examination showed eyelid and leg edema, and laboratory tests revealed hypoalbuminemia and acute kidney injury. After undergoing contrast-enhanced computed tomography, the patient was diagnosed with multiple arterial thrombosis (including the bilateral iliac arteries) due to nephrotic syndrome. Despite the performance of surgical thrombectomies, fasciotomy, and systematic heparinization, she required bilateral above-knee amputation. The patient achieved spontaneous remission of nephrotic syndrome, and her renal function fully recovered. There were no findings suggestive of secondary nephrotic syndrome and antiphospholipid syndrome. Her protein C and protein S concentrations were slightly decreased at admission. However, whole-exome sequencing revealed a thrombotic risk variant (T630I) in the PROS1 gene encoding protein S. This missense variant is often reported in patients with thrombosis or protein S deficiency, and may result in a thrombotic predisposition in some situations, such as undiagnosed nephrotic syndrome. Conclusions Arterial thrombosis is a rare complication; however, it must be considered, especially in patients with new-onset nephrotic syndrome. Early recognition is important for early intervention and prevention of serious sequelae.